2018
DOI: 10.3747/co.25.3816
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angiosarcoma of the Breast—Series of 11 Consecutive Cases—A Single-Centre Experience

Abstract: Angiosarcomas of the breast are rare parenchymal malignancies of the chest wall. Surgery is the main treatment modality with chemotherapy and radiotherapy used in case of recurrence. With generally unfavourable prognosis and lack of clear treatment guidelines due to its rarity and scarcity of available data, angiosarcoma of the breast is a challenging clinical situation for both oncologist and patient. We present here the results of a series of 11 consecutive primary angiosarcoma cases treated at our institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…Majority of the previous studies on this disease have been focused exclusively [1-3, 8, 11, 14] on Western populations. Additionally, there are a limited number of analyses that have a sufficiently large cohort or an Asian perspective [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the previous studies on this disease have been focused exclusively [1-3, 8, 11, 14] on Western populations. Additionally, there are a limited number of analyses that have a sufficiently large cohort or an Asian perspective [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Breast angiosarcomas are extremely rare malignancies that are responsible for only 0.05% of all malignant breast tumors [ 4 ]. Knowledge of this type of malignant neoplasm is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary lymph node resection is not recommended due to the low rate of lymph node metastasis, however due to a possibility of lymph node metastases up to 6.1% [ 20 ], sentinel lymph node biopsy was performed in the present case. Surgery may be complemented with adjuvant radiotherapy and chemotherapy for high-grade tumors, although the efficacy of either technique is still not clear [ 4 , 5 , 9 , 11 ]. In the present case, radical surgery was performed and adjuvant chemotherapy with paclitaxel was initiated, due to the high histologic grade of the tumor and pectoralis major muscle infiltration, although some authors have shown that the schedule with doxorubicin plus ifosfamide was associated with improved of progression free survival compared to anthracycline [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary tumors are associated with chronic lymphaedema in the upper limb after axillary lymph-node dissection and radiotherapy in patients with mammary carcinoma. The condition is known as Stewart-Treves syndrome [4,8,13,14] . Secondary angiosarcoma is also considered a complication from radiotherapy and breast-conserving surgery (BCS) in patients with breast carcinoma [15] .…”
Section: Introductionmentioning
confidence: 99%